Dicotomías documentadas: las obras de Kseniia Khrabrykh como la ventana hacia la Otredad - Anna BORISOVA (Fonseca, Journal of Communication, 2023)
The conceptual dichotomies «masculine-feminine», «Self-Other» structure our reality by leaving out any hybrid phenomenon and, therefore, foment inequalities. In the present essay we analyse the expressive strategies that are used in the documentaries ‘Art of Being Yourself’, ‘The Word’ and ‘Vidimo-Nevidimo’ by Kseniia Khrabrykh, an emerging Russian artist who challenges the dichotomous cognitive schemes, creates a symbolic space of encounter with Otherness and thus promotes empathetic and tolerant attitudes towards the inherent social diversity.